2018
DOI: 10.1136/oemed-2018-105050
|View full text |Cite
|
Sign up to set email alerts
|

Physical work exposure, chronic musculoskeletal pain and risk of insomnia: longitudinal data from the HUNT study, Norway

Abstract: ObjectivesTo prospectively investigate (i) the association of physical work demands and work-related physical fatigue with risk of insomnia symptoms and (ii) if these associations are influenced by chronic musculoskeletal pain.MethodsProspective study on a working population of 8563 women and 7598 men participating in the Nord-Trøndelag Health Study (Norway) who reported no insomnia at baseline in 1995–1997. Occurrence of insomnia symptoms was assessed at follow-up in 2006–2008. A Poisson regression model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…Esse dado mostra a relação da fadiga auto-referida com os sintomas físicos experenciados pelos entrevistados. A fadiga é, portanto, não apenas uma consequência do trabalho excessivo, mas também uma causa de sintomas osteomusculares relacionados ao trabalho que atinge não só o sistema muscular, como também pode estar relacionado a insônia e dor crônica, diminuindo assim, a qualidade de vida dos trabalhadores 20 .…”
Section: Discussionunclassified
“…Esse dado mostra a relação da fadiga auto-referida com os sintomas físicos experenciados pelos entrevistados. A fadiga é, portanto, não apenas uma consequência do trabalho excessivo, mas também uma causa de sintomas osteomusculares relacionados ao trabalho que atinge não só o sistema muscular, como também pode estar relacionado a insônia e dor crônica, diminuindo assim, a qualidade de vida dos trabalhadores 20 .…”
Section: Discussionunclassified
“…Longitudinal population-based studies, as summarized by Finan et al [ 119 ] and Smith et al [ 120 ], indicate that sleep disturbances, most commonly insomnia, may predate the development of chronic regional and widespread pain. Although the association between insomnia and musculoskeletal pain is well documented [ 121 , 122 , 123 ], we found only one study exploring the association with MPS. In this prospective study, 7895 participants (1579 patients with insomnia and 6316 controls) who were selected from the Taiwan National Health Insurance Research Database were observed for a maximum of 10 years to determine the incidence of newly diagnosed MPS.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were asked to report the frequency of stress at work, and the response options were four-point categorical scale: (1) never; (2) some periods; (3) several periods; (4) permanent stress. Regarding the assessment of work-related physical fatigue, it was based on the method of Skarpsno et al [23]. Participants were asked: 'Is your work so physically demanding that you are often physically worn out after a day's work?…”
Section: Assessment Of Associated Variablesmentioning
confidence: 99%